Proteasome, but not autophagy, disruption results in severe eye and wing dysmorphia: a subunit- and regulator-dependent process in Drosophila. - Velentzas, P.D.; Velentzas, A.D.; Pantazi, A.D.; Mpakou, V.E.; Zervas, C.G.; Papassideri, I.S.; Stravopodis, D.J. (PLoS ONE, 2013)
Proteasome-dependent and autophagy-mediated degradation of eukaryotic cellular proteins represent the two major proteostatic mechanisms that are critically implicated in a number of signaling pathways and cellular processes. Deregulation of functions engaged in protein elimination frequently leads to development of morbid states and diseases. In this context, and through the utilization of GAL4/UAS genetic tool, we herein examined the in vivo contribution of proteasome and autophagy systems in Drosophila eye and wing morphogenesis. By exploiting the ability of GAL4-ninaE. GMR and PGawBBx(MS1096) genetic drivers to be strongly and preferentially expressed in the eye and wing discs, respectively, we proved that proteasomal integrity and ubiquitination proficiency essentially control fly's eye and wing development. Indeed, subunit- and regulator-specific patterns of severe organ dysmorphia were obtained after the RNAi-induced downregulation of critical proteasome components (Rpn1, Rpn2, ?5, ?5 and ?6) or distinct protein-ubiquitin conjugators (UbcD6, but not UbcD1 and UbcD4). Proteasome deficient eyes presented with either rough phenotypes or strongly dysmorphic shapes, while transgenic mutant wings were severely folded and carried blistered structures together with loss of vein differentiation. Moreover, transgenic fly eyes overexpressing the UBP2-yeast deubiquitinase enzyme were characterized by an eyeless-like phenotype. Therefore, the proteasome/ubiquitin proteolytic activities are undoubtedly required for the normal course of eye and wing development. In contrast, the RNAi-mediated downregulation of critical Atg (1, 4, 7, 9 and 18) autophagic proteins revealed their non-essential, or redundant, functional roles in Drosophila eye and wing formation under physiological growth conditions, since their reduced expression levels could only marginally disturb wing's, but not eye's, morphogenetic organization and architecture. However, Atg9 proved indispensable for the maintenance of structural integrity of adult wings in aged flies. In toto, our findings clearly demonstrate the gene-specific fundamental contribution of proteasome, but not autophagy, in invertebrate eye and wing organ development.